A propriedade intelectual nas Forças Armadas brasileiras : um paralelo entre a Marinha, Exército e Aeronáutico quanto aos depósitos de patentes e as políticas de criação dos NITs - Dall´agnol, Rogéria Prado (2015)
Intellectual property has become fundamental and strategic tool for economic development of a country. Organizations, in its various branches, have invested diuturnamente in new ideas through research, technological development and innovation, taking advantage of legal protection to protect their inventions. In the new paradigm economic technical, based on knowledge, technological innovation, aligned with the intellectual property protection, contributes to major technological and economic development of countries. In this sense, there is the capacity of institutions such as the armed forces of Brazil, to make research, development and innovation. The present study is a survey of the Marine intellectual property protection, Army and Air Force through the number of patent applications in order to identify, within these institutions, where there is greater integration of intellectual property and compares the situation of its Technological Innovation Centers - NIT. We used the methodology bibliographical and documentary research and empirical analysis of patent deposits numbers by searching on the basis of patents of the National Institute of Industrial Property (INPI) in the period from 1976 to 2014. It was possible to identify the temporal evolution of deposits patent applications. It was found that the Air Force is the center of Brazil with the highest number of patent deposits and the Brazilian Army the least deposits. The performance of the NIT Army is still very incipient. There are numerous unanswered questions regarding the situation of Brazil and its armed forces regarding their NITs and their technological productions. The understanding that innovation and intellectual property are key factors for the development of a country instigate further research in this field.